USM-KLE INDIA ASSISTS IN POLIO VACCINATION PROGRAMME IN INDIA - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 19 January 2016 40 students of Universiti Sains Malaysia (USM) currently undergoing the USMKarnataka Lingayat Education (KLE) International Medical Programme (IMP) in India participated in the polio vaccination programme to thousands of people in India throughout the vicinity of Belgaum, India recently.